Chicken innate immune response to oral infection with Salmonella enterica serovar Enteritidis - Matulova, Marta; Varmuzova, Karolina; Sisak, Frantisek; Havlickova, Hana; Babak, Vladimir; Stejskal, Karel; Zdrahal, Zbynek; Rychlik, Ivan (Veterinary research, 2013)
The characterization of the immune response of chickens to Salmonella infection is usually limited to the quantification of expression of genes coding for cytokines, chemokines or antimicrobial peptides. However, processes occurring in the cecum of infected chickens are likely to be much more diverse. In this study we have therefore characterized the transcriptome and proteome in the chicken cecum after infection with Salmonella Enteritidis. Using a combination of 454 pyrosequencing, protein mass spectrometry and quantitative real-time PCR, we identified 48 down- and 56 up-regulated chicken genes after Salmonella Enteritidis infection. The most inducible gene was that coding for MMP7, exhibiting a 5952 fold induction 9 days post-infection. An induction of greater than 100 fold was observed for IgG, IRG1, SAA, ExFABP, IL-22, TRAP6, MRP126, IFNγ, iNOS, ES1, IL-1β, LYG2, IFIT5, IL-17, AVD, AH221 and SERPIN B. Since prostaglandin D2 synthase was upregulated and degrading hydroxyprostaglandin dehydrogenase was downregulated after the infection, prostaglandin must accumulate in the cecum of chickens infected with Salmonella Enteritidis. Finally, above mentioned signaling was dependent on the presence of a SPI1-encoded type III secretion system in Salmonella Enteritidis. The inflammation lasted for 2 weeks after which time the expression of the "inflammatory" genes returned back to basal levels and, instead, the expression of IgA and IgG increased. This points to an important role for immunoglobulins in the restoration of homeostasis in the cecum after infection.
Keywords: Sequence Analysis, DNA; nemoci úst; cékum; Salmonella enteritidis; transkriptom; polymerázová řetězová reakce; nemoci drůbeže; Gene Expression Regulation; Immunity, Innate; Polymerase Chain Reaction; Avian Proteins; Mass Spectrometry; Transcriptome; kur domácí; regulace genové exprese; přirozená imunita; Mouth Diseases; Chickens; Proteome; zvířata; Poultry Diseases; ptačí proteiny; northern blotting; sekvenční analýza DNA; proteom; Cecum; Blotting, Northern; salmonelová infekce u zvířat; hmotnostní spektrometrie; Salmonella Infections, Animal; Animals